EFEKTIVITAS TEKNIK SHOW NOT TELL DENGAN BANTUAN MEDIA GAMBAR DALAM MENULIS TEKS CERITA FABEL PADA SISWA SMP KELAS VII - Moch Ichsan Nugraha; Wahyu Hidayat; Mimin Sahmini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research investigates the impact of applying the Show Not Tell strategy, enhanced through the use of visual media, on the development of fable writing skills among seventh-grade students. The study is motivated by the noticeable challenges students face in crafting well-structured narratives, particularly in areas such as character portrayal, narrative flow, and plot clarity. Adopting a quantitative methodology, the study utilized a one-group pretest-posttest model involving 20 students from SMP Negeri 2 Margaasih. Writing assessments were conducted before and after the intervention, with the resulting data analyzed through normality testing, paired sample t-tests, and N-Gain calculations using SPSS software. Findings indicate a significant improvement, with the mean score rising from 46.40 in the pretest to 80.10 in the posttest. The paired t-test produced a p-value of 0.000 (p < 0.05), confirming a meaningful statistical difference in students’ performance following the intervention. The N-Gain score was 0.6278 (62.78%), categorized as moderate with an interpretation of being reasonably effective. These findings demonstrate that the Show Not Tell technique, supported by visual media, positively impacts students’ ability to write fable texts.